Cartilha de prompts: o uso de inteligência artificial generativa no planejamento pedagógico do ensino de história - Aragão, Rômulo Gois de (2025)
This work aims to contribute to the pedagogical planning of History teaching using Generative Artificial Intelligence (GenAI), specifically ChatGPT. The research focuses on studying the potential of ChatGPT in History education, proposing a "Prompt Guide" as a product to assist other teachers in understanding and creating prompts. As an example, the tool was tested in designing activities for the First Quarter of the 1st year of high school. The goal is to make the mechanical tasks of teaching less exhausting, fostering a small degree of teacher (self)development. This work will consider the competencies and skills outlined in the National Common Curricular Base (BNCC), the National Curriculum Parameters (PCN), and the Bahia Curricular Reference Document (DCRB), aligning with the concept of "Historical Consciousness" (Rüsen, 2015). The research concludes that it is possible to integrate History teaching and Artificial Intelligence, provided there are adequate technical and structural conditions, as well as proficiency in competencies related to digital literacy, multiliteracies, and a transdisciplinary perspective on the part of History teachers.